From genes to function: the next challenge to understanding multiple sclerosis. - Fugger, L; Friese, M; Bell, J (2009)
Susceptibility to multiple sclerosis is jointly determined by genetic and environmental factors, and progress has been made in defining some of these genetic associations, as well as their possible interactions with the environment. However, definitive proof for the involvement of specific genetic determinants in the disease will only come from studies that examine their functional roles in disease pathogenesis. New and combined approaches are needed to analyse the complexity of gene regulation and the functional contribution of each genetic determinant to disease susceptibility or pathophysiology. These studies should proceed in parallel with the use of genetically defined human populations to explore how both genetic and environmental factors affect the function of the pathways in individuals with and without disease, and how these determine the inherited risk of multiple sclerosis.